Analysis of The Effect of Covid-19 Towards L2 English Speaking Performance - Djafar, Rahmi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Speaking is one of important factors in communicating. Like English Speaking as a international language and student and lecturer must know how to apply it . Students need to practice after found the treatment from lecturer, face to face. But, teaching Speaking in current situation of Pandemic Covid-19, face some obstacle on it. The pandemic made as have to social distancing and online learning. This research aims to analysis the effect of Covid-19 toward L2 speaking performance which can improve speaking ability on this pandemic, even in difficult situations like learning by virtual. This research method is descriptive research. Conducted by using google form or online. The findings result of this research, was English speaking class in Pandemic Covid-19, more difficult, then normal era. Students or teacher cannot here clearly, about discussion. It was depending on signal as a technology product. Besides, students lack of vocabularies and did not know of pronounce some vocabularies.